An Analysis of Socio-Culturally-Bound Expressions in Indonesian-English Translation of English Education Department Students - Widhiya Ninsiana; Syahreni Siregar; Indah Meylisa (STAI Hubbulwathan Duri, 2022)
The objectives of this research are to know the students’ difficulties in translating the socio-culturally-bound Expressions in Indonesian- English translation, and to analyze the causes of students in translating the socio-culturally-bound Expressions in Indonesian-English translation. This study used a qualitative research method in the form of a case study conducted at IAIN Metro. The primary source of this research was the translation assignment results of IAIN Metro students in the academic year 2020/2021. There were a total of 20 students who participated in the research. In order to collect data, the researchers used documentation and interview techniques. The research concluded that students' translations of socioculturally bound expressions in Indonesian-English translations consist of 85 % inappropriate use of sociocultural bound expression and 15 % appropriate use of a sociocultural bound expression. Furthermore, the second research result is about the causes of the students' difficulties in translating socioculturally bound expressions in Indonesian-English translation affected by the translator's lack of knowledge in both languages in general and in the significance of functional equivalence in particular, limited linguistic competence, their poor pragmatic competence in the target language, lack of cultural awareness, and lack of cultural interaction and equivalence.